Development of a deep learning model for predicting recurrence of hepatocellular carcinoma after liver transplantation - Ko, Seung Hyoung; Cao, Jie; Yang, Yong-kang; Xi, Zhi-feng; Han, Hyun Wook; Sha, Meng; Xia, Qiang (Frontiers in Medicine, 2024)
Liver transplantation (LT) is one of the main curative treatments for hepatocellular carcinoma (HCC). Milan criteria has long been applied to candidate LT patients with HCC. However, the application of Milan criteria failed to precisely predict patients at risk of recurrence. As a result, we aimed to establish and validate a deep learning model comparing with Milan criteria and better guide post-LT treatment.A total of 356 HCC patients who received LT with complete follow-up data were evaluated. The entire cohort was randomly divided into training set (n=286) and validation set (n=70). Multi-layerperceptron model provided by pycox library was first used to construct the recurrence prediction model. Then tabular neural network (TabNet) that combines elements of deep learning and tabular data processing techniques was utilized to compare with Milan criteria and verify the performance of the model we proposed.Patients with larger tumor size over 7cm, poorer differentiation of tumor grade and multiple tumor numbers were first classified as high risk of recurrence. We trained a classification model with TabNet and our proposed model performed better than the Milan criteria in terms of accuracy (0.95 vs. 0.86, p<0.05). In addition, our model showed better performance results with improved AUC, NRI and hazard ratio, proving the robustness of the model. Conclusion A prognostic model had been proposed based on the use of TabNet on various parameters from HCC patients. The model performed well in post-LT recurrence prediction and the identification of highrisk subgroups.